Nationwide Survey of Association Between Fever and Epileptic Seizure in CDKL5 Deficiency Disorder Revealed Therapeutic Implications - Siyi Wang; Jialin Du; Jinghui Liu; Dongmei Hu; Hongxin Wang; Xiaoxiao Man; Lehong Gao; Shimin Hu; Xianghong Meng; Hongyang Zhao; Minjing Hu; Yingxue Yang; et al. (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Objective CDKL5 deficiency disorder (CDD) is a rare, severe developmental and epileptic encephalopathy. There is a pressing need to develop effective and sustainable therapeutic strategies. We aimed to investigate the causal association between febrile episodes and epileptic seizures for therapeutic implications in CDD patients. Methods The study was a nationwide, cross‐sectional survey on CDD patients in China ( ClinicalTrials.gov , NCT06663163). Detailed phenotypic and genotypic data were collected through an online questionnaire with uploaded original medical records, genetic testing results, and peri‐fever seizure diaries. The primary outcome was changes in epileptic seizure frequency during and post‐fever phases compared to a 1‐month pre‐fever phase based on seizure diaries. Results Between October 2024 and December 2024, we received 131 questionnaires. Forty‐seven questionnaires were removed after excluding duplicates and missing data. Ultimately, 84 eligible participants with complete uploads were included, from 26 of 34 (76.5%) province‐level regions in China. Among these, 47 (56.0%) patients had significant decreased seizure frequency only during febrile episodes, and 27 (32.1%) patients with daily seizures achieved at least a seizure‐free day. Notably, 20 patients (23.8%) exhibited post‐fever seizure reduction: 12 (25.5%) for 3 days to 1 week, and 6 (12.8%) for more than 2 weeks (maximum > 40 days). The effect was independent of patients' clinical and genetic characteristics. Interpretation Our findings, for the first time, revealed that fever‐related seizure reduction is a distinctive and prevalent genotype–phenotype for CDD, thereby providing evidence for further fundamental research into the underlying mechanisms and offering potential clinical implications for seizure control in CDD.